2001
DOI: 10.1079/phn2001173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sugars and micronutrient dilution in normal adults aged 65 years and over

Abstract: Objective: To examine the relationship between non-milk extrinsic sugars (NMES) concentration and micronutrient intakes and status in free-living older people. Design: The National Diet and Nutrition Survey of people aged 65 years and over; a cross-sectional study in Britain in 1994/5. Subjects and methods: Eight hundred and six men and women living in private households who were not on medication for nutritional disorders. Subjects were classified into four groups (Q1 to Q4), using cut-off points correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 25 publications
(19 reference statements)
4
34
4
Order By: Relevance
“…Similar to findings reported in British elderly (Gibson, 2001), energy intake explained between 20 and 64% of the variance in intake of folate, calcium, vitamin B6, zinc, iron and thiamin, while intake from added sugar (in absolute amounts) explained, at most, 2%. Energy intake explained much less of the variance in the intake of vitamins A, B 12 , C and D, but the positive association remained significant (in women).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Similar to findings reported in British elderly (Gibson, 2001), energy intake explained between 20 and 64% of the variance in intake of folate, calcium, vitamin B6, zinc, iron and thiamin, while intake from added sugar (in absolute amounts) explained, at most, 2%. Energy intake explained much less of the variance in the intake of vitamins A, B 12 , C and D, but the positive association remained significant (in women).…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, evidence of micronutrient dilution in diets high in added sugar have been reported for adults by Bowman (1999) and Gibson (1997). In the elderly, Charlton et al (1998) have demonstrated an inverse relationship between the intake of most micronutrients and consumption of sugars in mixed ancestry South Africans, while Gibson (2001) found little evidence that poorer nutrient status was associated with higher levels of dietary nonmilk extrinsic sugars in British elderly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations